2017
DOI: 10.1186/s12864-017-3544-6
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis reveals complex regulatory properties at Taf14-repressed genes

Abstract: BackgroundRegulation of gene transcription in response to stress is central to a cell’s ability to cope with environmental challenges. Taf14 is a YEATS domain protein in S.cerevisiae that physically associates with several transcriptionally relevant multisubunit complexes including the general transcription factors TFIID and TFIIF and the chromatin-modifying complexes SWI/SNF, INO80, RSC and NuA3. TAF14 deletion strains are sensitive to a variety of stresses suggesting that it plays a role in the transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 55 publications
(97 reference statements)
1
8
0
Order By: Relevance
“…6 ). This is consistent with earlier observations that Snf2, Snf5 and Taf14 are involved in the stress alleviation 64 , 65 . Other than this, diverse responses of swi1∆ and [ SWI + ] cells to a variety of chemical stresses highlights the complexity of ESR mediated by the Swi1 prion and its null mutant.…”
Section: Discussionsupporting
confidence: 94%
“…6 ). This is consistent with earlier observations that Snf2, Snf5 and Taf14 are involved in the stress alleviation 64 , 65 . Other than this, diverse responses of swi1∆ and [ SWI + ] cells to a variety of chemical stresses highlights the complexity of ESR mediated by the Swi1 prion and its null mutant.…”
Section: Discussionsupporting
confidence: 94%
“…Indeed, the Snf2 catalytic subunit of SWI/SNF was shown to be recruited to response of the genes under osmotic stress by means of the Cyc8-Tup1 regulatory network [75], and this recruitment is positively affected by kinases of the PKA family [76]. In addition, the sets of genes misregulated by deletions of SWI2 and TAF14 that encode the transcriptional regulator involved in the stress alleviation overlap significantly [77]. However, it does not explain why most of the response types are positively modulated in the swi1 Δ cells, while the oxidative stress response is repressed.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast cells devoid of Taf14 have defects in actin organization, morphology, and cytoskeleton formation and show increased sensitivity to temperature, osmotic stress, and DNA‐damaging agents (Henry et al, 1994; Nemet et al, 2017; Welch et al, 1993). Structural analysis revealed that the acylated H3K9 peptide is sandwiched in an aromatic cage formed by two aromatic residues, phenylalanine at position 62 (F62) and tryptophan at position 81 (W81), and mutation of W81 can disrupt the interaction between the YEATS domain and the H3K9ac peptide (Shanle et al, 2015).…”
Section: Discussionmentioning
confidence: 99%